4CPS-195 Pharmacist interventions: the success of an antimicrobial stewardship team. (March 2019) - Duarte, H; Costa, G; Azevedo, S; Andreozzi, V; Felix, J; Coelho, M; Alcobia, A
Abstract : Background: Pharmacist involvement in antibiotic stewardship helps to ensure compliance with the standards set by the National Health Service. Collection and evaluation of antimicrobial utilisation data are important for assessing the impact of antibiotic stewardship intervention in hospitals. Purpose: Reduce number of inappropriate prescriptions, duration of antibiotic therapy and, therefore, decrease the antimicrobial resistance. Material and methods: Prospective study in a single centre. The antibiotics prescriptions between June 2015 and February 2017 were screened by a pharmacist who checked all prescriptions and sent to the antimicrobial stewardship physicians the ones without approval of therapeutic protocols or analytical results. Statistical analysis was performed using R Studio 3.5.1 (5% significance level). Results: We identified 1242 patients with mean (SD) age of 67.9 (16.6) years and 54.5% males, resulting in 1027 prescriptions of carbapenems (67.2%) and 502 prescriptions of quinolones (32.8%). The most common site of infection was the urinary tract, accounting for 28% of prescriptions. According to the prescribed therapeutic intervention, 261 (17%) were empirical prescriptions, 518 (33.9%) inappropriate prescribing, 489 (31.9%) documented and 258 (16.8%) were according to the protocol approved by the institution. The physician's acceptance of pharmacy interventions was 52.5%. The mean treatment duration varied according to type of prescription: 9 days for documented prescription; 8.1 days for empirical prescriptions; 6.3 days for prescriptions according to protocol; and 5.5 days for inappropriate prescriptions (p=0.0001). The interventions reduced the mean duration of therapy: 5.5 days for prescriptions with intervention and 7.6 days for the ones without (p<0.0001). It was found that in 652 prescriptions with microbial isolates, 369 were multidrug-resistant microorganisms (24.1%). Patients who were discharged early with antibiotics for ambulatory care (21.7%) had lower mean duration of treatment (5.8 days) and a lower proportion of multidrug-resistant strains (42.5%) than patients who were discharged without antibiotics (56.6%; 7.7 days and 62.9%) or patients who died (14.6%; 7.1 days; 52.2%) (p=0.0001). Conclusion: Pharmacy-driven interventions could be a strategy for decreasing costs with human resources associated with antimicrobial stewardship due to the effective screening of antibiotics prescriptions. Investment in the surveillance results in early hospital discharge with a shorter length of antibiotic treatment with a consequent decreasing of multidrug-resistant strains. References and/or acknowledgements: Exigo Consultores. No conflict of interest.